The relationship between a fish-rich diet and poststroke cognitive impairment: A cross-sectional study with a follow-up in China. Issue 25 (24th June 2022) - Li, Jia-Rui; Yu, Yang; Meng, Fan-Xia; Yu, Jie; Luo, Ben-Yan; Gao, Jian
Abstract : Abstract: Whether a fish-rich diet is positively associated with cognitive function after stroke remains unclear; thus, the present study investigated the relationship between them. The present study was part of a prospective multicenter study, in which 920 individuals (609 males, mean age, 62.78 ± 11.79 years) were included from November 2013 to December 2015. The cognitive function of the patients was evaluated, and the diagnosis of poststroke cognitive impairment (PSCI) was made during their stay in the hospital. A subgroup of 439 patients from a single center was followed up for 4 to 6 years and was reassessed for cognitive function. According to the diagnostic criteria, the PSCI prevalence was lower in the fish-rich diet group ( P  < .05). After adjusting for demographic and clinical variables by logistic regression, patients with a habit of consuming a fish-rich diet had a lower risk of developing PSCI than patients without a fish-rich diet (odds ratio [OR]: 0.74; 95% confidence interval [CI]: 0.46–0.95). When MMSE score was considered the cognitive function outcome variable, the long-term cognitive function of the fish-rich diet group was better (28 [26–30] vs 27 [25–29], P  < .01), but the statistical results were not significant after correcting for the related confounding factors (β: 0.13; 95% CI: −0.99–1.25; P  = .82). There was a negative relationship between consuming a fish-rich diet and the prevalence of PSCI, and there was no statistically significant difference in the relationship of a fish-rich diet on long-term cognitive function after stroke, which requires further study.